Chinese Herbal Medicine for Irritable Bowel Syndrome: A Meta-Analysis and Trial Sequential Analysis of Randomized Controlled Trials - Zheng, Hui; Jin, Song; Shen, Yin-Li; Peng, Wen-Yan; Ye, Kun; Tang, Tai-Chun; Zhao, Jun; Chen, Min; Li, Zhi-Gang (Frontiers in Pharmacology, 2021)
Purpose: Chinese herbal medicine (CHM) is an important complementary and alternative therapy for the management of irritable bowel syndrome (IBS). Previous meta-analyses suggested that CHM is effective for IBS; nonetheless, its effectiveness is inconclusive owing to repeated significance testing. We aimed to examine the efficacy and safety of CHM for IBS through a meta-analysis and trial sequential analysis (TSA). Methods: We searched OVID Medline, Embase, Cochrane Central Register of Controlled Trials, and Web of Science from January 1, 1980, to September 20, 2020. The primary outcome was adequate relief of global IBS symptoms. The secondary outcomes included relief of abdominal pain and treatment-related adverse events. The relative ratio (RR) and required information size (RIS) were calculated for each outcome. Results: Ten trials recruiting 2,501 participants were included. Seven (70%) trials were at low risk of bias (RoB). Compared with placebo, CHM was associated with a significantly higher proportion of adequate relief of global IBS symptoms [RR 1.76 (95% confidence interval (95%CI), 1.33–2.33); I2 = 81.1%; p < 0.001]. The RIS was 1,083 for the primary outcome, and the accrued information size was 1,716. The analysis of the relief of abdominal pain (three trials with 916 participants) showed similar results compared with placebo [RR 1.85 (95%CI, 1.59–2.14); I2 = 0%; p < 0.001; RIS = 197 participants]. CHM was associated with a higher proportion of adverse events compared with placebo [RR 1.51 (95%CI, 1.14–2); I2 = 0%; p = 0.004]. Conclusion: CHM was effective in relieving IBS symptoms but caused a higher adverse event rate than placebo. TSA analysis confirmed the findings with sufficient information size.